The effect of cationic surfactants on bitumen's viscosity and asphaltene nanostructure under thermal partial upgrading. Issue 7 (4th April 2022) - Abdrabou, Moataz K.; Han, Xue; Zheng, Ying; Zeng, Yimin; Rohani, Sohrab
Abstract: Bitumen extracted from oil sands is a highly viscous fluid; thus, its transportation via pipelines in its original form resembles a major challenge. Partial upgrading is a recently proposed approach that aims to reduce bitumen's viscosity to meet the pipeline specifications. To optimize the process and make it more cost‐effective, a novel approach is proposed and researched in this study. Ionic surfactants were for the first time employed to promote thermal cracking reactions and dispersion of asphaltenes in bitumen at elevated upgrading temperatures. Three surfactants representing the cationic, nonionic, and anionic charges were studied at the thermal upgrading conditions (360–400 ◦ C) at their optimal addition ratios to mimic the bitumen partial upgrading conditions. The results demonstrated that the cationic surfactant (dodecyltrimethylammonium bromide, DTAB) surpassed the other two surfactants and that with the addition of only 0.25 wt% of it, it can effectively reduce the viscosity of bitumen by up to 60% more than the upgraded bitumen with no additives under the same upgrading temperature. The Saturates, Aromatics, Resins, and Asphaltene analysis revealed that the contents of saturates and aromatics within the upgraded bitumen were also enhanced when DTAB was added. Moreover, the detailed asphaltene nanostructural analysis using X‐ray diffraction, high‐resolution transmission electron microscope, and thermogravimetric analysis revealed that the addition of the cationic surfactant (DTAB) resulted in an increased asphaltene nanostructural disorder, smaller polycyclic aromatic hydrocarbons size, and increased fringe curvature, as compared with the upgraded bitumen's asphaltene with no surfactants. Hence, the results have suggested that DTAB, a cheap and readily available ionic surfactant, can serve as a potential upgrading additive for designing partial upgrading procedures to produce upgraded bitumen with much less viscosity at lower upgrading temperatures. This upgrading technique will result in an upgraded bitumen that requires significantly reduced volumes of diluent for transportation. Abstract : Cationic surfactants were first identified to be effective in reducing the bitumen viscosity. The suggested crude oil upgrading procedure in the study resulted in a decrease in fringe length of asphaltene, suggesting the addition of surfactant offers advantages in thermal upgrading.